A comparative study of intrathecal and epidural buprenorphine using combined spinal-epidural technique for caesarean section - Ipe, Shaloo (Medknow Publications, 2010)
Neuraxial opioids provide excellent analgesia intraoperatively and postoperatively while allowing early ambulation of the patient by sparing sympathetic and motor nerves. A prospective, randomised double blind study was conducted involving 90 patients of ASA 1 physical status coming for elective cesarean section to evaluate the analgesic effect of neuraxial buprenorphine. They were allocated into three groups. Spinal local anaesthetic was used as the main stay of anaesthesia for surgery and spinal and epidural analgesia with opioids continued as the main stay for postoperative analgesia. All the groups were given 0.5% Bupivacaine intrathecally for the surgery. Besides this, group I was given 150 mcg Buprenorphine intrathecally and group II and III were given 150 mcg and 300 mcg Buprenorphine respectively, epidurally. In the present study, we observed that 150 mcg of Buprenorphine given intrathecally provided much longer duration of analgesia compared to 150 mcg of Buprenorphine given epidurally. Increasing the epidural dose of Buprenorphine from 150 mcg to 300 mcg proved to produce prolonged analgesia comparable to intrathecal Buprenorphine without compromising patient safety and neonatal outcome. The minor side effects were more with intrathecal Buprenorphine than epidural Buprenorphine. We concluded that 300 mcg of Buprenorphine epidurally is equianalgesic to 150 mcg Buprenorphine intrathecally.